Optimal Organization of Financial Intermediaries - Spiros Bougheas; Tianxi Wang (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper provides a unified framework for endogenizing two distinct organizational structures of financial intermediation. In one structure, called Bank, the intermediary is financed by issuing debt contracts to investors, and thus resembles commercial banks. In the other structure, called Fund, the intermediary is financed by issuing equity contracts to investors, thus resembling private-equity funds. The paper finds that in the former incentives can be provided in a less costly way, but the latter is more robust to negative shocks on the asset side. Our model predicts that relative to banks, private equity funds are more involved in the running of the firms that they finance, contribute more to the success of these firms, and provide funds to higher-risk, higher-return firms.
Keywords: D86; G00; 330; financial intermediation; bank; equity funds